Unilateral Lung Agenesis in an infant with prenatal diagnosis of Congenital Lobar Emphysema - Olivia Ganescu; Robin T. Petroze; Pramod S. Puligandla (Elsevier, 2020)
Infants in respiratory distress presenting with congenital lobar emphysema (CLE) are surgical emergencies. However, several other congenital lung lesions (CLL) have similar prenatal imaging, highlighting the importance of early postnatal evaluation. We present a case of a newborn transferred for respiratory distress. Prenatal imaging suspected a CLE in the left upper lobe with concern for decompensation in the early postnatal period. Upon arrival, the patient demonstrated reasonable cardio-respiratory stability after initial apnea and cyanosis; due to prenatal concerns, we proceeded to CT imaging, which demonstrated congenital absence of the right pulmonary artery, agenesis of the right lung, and a larger left lung herniating into the right side. Surgical intervention was therefore not required. This case emphasizes the importance of postnatal imaging in the CLL workup. Providing "pathological" diagnoses to CLL can affect postnatal counseling and influence surgical decision-making. Here, early postnatal imaging clarified the diagnosis and prevented both unnecessary surgery and significant morbidity. The patient's clinical status should determine the urgency of CLL investigation. Stable patients may be followed as outpatients but should be assessed within 1-2 weeks after birth. Symptomatic patients should be transferred to tertiary care centers with pediatric surgical expertise for further investigation and possible intervention. Keywords: Prenatal diagnosis, Congenital lung lesions, Pulmonary agenesis, Congenital lobar emphysema